Temperature determination at the chip-tool interface using a computational fluid dynamics package. (30th April 2019) - Chowdhury, S.A.; Islam, M.N.; Boswell, B.
This paper presents the development of a methodology for determining the chip-tool interface temperature distribution in flood turning using a Computational Fluid Dynamics (CFD) package. The methodology begins with estimation of heat generated during the cutting process, then geometrical representation of the metal cutting process and mesh development. A CFD analysis is used to determine the chip-tool interface temperature distribution. The methodology developed was validated by comparing predicted chip-tool interface temperature with measured temperature taken from three sources available in the literature. Numerical experiments for three different materials were conducted to establish the relationships between the flow rate of the cutting fluid and chip-tool interface temperature. The results indicate that when the cutting fluid flow rate is increased beyond a certain level its effect diminishes.